TORSION PENDULUM DYNAMIC CHARACTERISTICS STUDY OF SCRAPER CHAIN SYSTEM OF SCRAPER CONVEYOR - MAO Jun; WANG Xin; CHEN HongYue; ZHANG Yu (Jixie qiangdu)
In order to investigate torsion pendulum dynamic characteristics of scraper chain system,dynamic model of scraper chain system was established by using finite element method.Numerical simulation was analyzed for dynamic characteristics of scraper chain system by applying pulse load,step load and slope load.Torsion pendulum dynamic characteristics of scraper chain system,dynamic response of chain and dynamic tension transfer characteristic of scraper were researched.The results show that scraper has a big angular displacement at bearing section,and has a big torsion moment.Angular displacement amplitude and torsion moment amplitude gradually reduce from bearing section to the sides.The results provide theoretical basis for dynamic design of scraper conveyor.